2019
DOI: 10.17135/jdhs.2019.19.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Commercial Effervescent Vitamin Tablets on Bovine Enamel

Abstract: Background: In this study, four types of effervescent vitamins marketed in Korea were analyzed for their acidity and vitamin content. For this purpose, bovine teeth were immersed in vitamin, and surface microhardness and appearance were measured before and after immersion to evaluate tooth demineralization and erosion. Methods: Bovine permanent incisors with sound surface enamel were cut to 5×5 mm size, embedded in acrylic resin, and polished using a polishing machine with Sic-paper. The prepared samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Although there isn’t a precise pH level upon which demineralization commences, it is assumed that a general pH range of 5.5–5.0 is requisite for tooth minerals to dissolve [ 39 ]. This agreed with Jeong et al, [ 40 ] who reported that medication with a low pH as well as high citric acid levels has an affinity for the tooth enamel, causing enamel erosion. Moreover, Rytömaa et al [ 41 ] specified that tooth enamel dissolves when a pH value equals 5.5, and acidic food with pH < 4 is most probably causing erosion.…”
Section: Discussionsupporting
confidence: 91%
“…Although there isn’t a precise pH level upon which demineralization commences, it is assumed that a general pH range of 5.5–5.0 is requisite for tooth minerals to dissolve [ 39 ]. This agreed with Jeong et al, [ 40 ] who reported that medication with a low pH as well as high citric acid levels has an affinity for the tooth enamel, causing enamel erosion. Moreover, Rytömaa et al [ 41 ] specified that tooth enamel dissolves when a pH value equals 5.5, and acidic food with pH < 4 is most probably causing erosion.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, severe surface changes were observed in groups 1 and 3, which had low pH. Jeong et al 26) studied the coloring and erosion of enamel surfaces by immersing premolars in commercially available oral brushing solutions and reported that the erosion pattern of enamel surfaces could be confirmed in all groups. In particular, erosion of the enamel surface was confirmed in the Nexcare and Listerine groups at low pH.…”
Section: )mentioning
confidence: 99%
“…reported that the intake of carbonated food products, acidic foods, and citrus fruits such as tangerines 25) as well as fizzy vitamin tablets had significant effects on dental erosion 26) . Choi and Shin 12) also reported that most beverages had an acidic pH: 2.96±0.30 for carbonated drinks, 3.29±0.37 for fruit juices, and 3.15±0.26 for electrolyte beverages.…”
Section: )mentioning
confidence: 99%